Adaptation of Inductive Power Transfer to Small Household Appliances That Can Operate on Induction Heating Cooktops: Wireless Electric Kettle - Sezer, Canberk; Altintas, Nihan (MDPI, 2023)
In this paper, an inductive power transfer (IPT) system without compensation elements is presented for small house appliances. The proposed system's transmitter side is an independent induction heating cooktop. IPT can be achieved when the kettle with the receiving coils is placed on the transmitter coil. The coils are designed with a high coupling coefficient. The magnetic system model consisting of aligned transmitter and receiver coils is created in the Maxwell program. In the created model, the analysis depends on the air gap and frequency, which are the variables that affect the wireless power transfer. The electronic circuit simulation uses the coil model to examine the system's dynamic behavior. The design of the transmitter/receiver coils of the IPT system is made with a cylindrical coil with a diameter of 145 mm, taking into account that it is compatible with the dimensions of the existing kettle and induction heating cooktops coil. A half-bridge series resonant converter circuit is used to adjust the power transferred to the load. To verify the simulation results and test the designed system, an experimental circuit using a 2200 W kettle is carried out. In the experiments, the air gap between the coils is kept constant at 7 mm, and measurements are taken for different powers. Experimental results confirm the magnetic model and simulation results. As a result, wireless power transfer is realized in a wide range without loss of performance in the kettle. System efficiency is greater than the 90% specified in the Ki cordless kitchen standard, and the harmonic currents drawn from the mains are lower than the values determined by the IEC 61000-3-2 standard.
Keywords: cordless kitchen appliances; domestic induction cooktops; IPT; WPT; wireless electric kettle; SYSTEM; Energy & Fuels